Anti–Jo-1 Syndrome Often Misdiagnosed as Rheumatoid Arthritis (for Many Years): A Single-Center Experience. Issue 4 (June 2021) - Kumar, Rajiv Ranjan; Jha, Saket; Dhooria, Aadhaar; Naidu, G.S.R.S.N.K; Minz, Ranzana W.; Kumar, Susheel; Sharma, Shefali Khanna; Sharma, Aman; Jain, Sanjay; Dhir, Varun
Abstract : Background: Antisynthetase syndrome is characterized by a triad of myositis, arthritis, and interstitial lung disease. Anti–Jo-1 is the most common associated autoantibody. This study planned to look at the presentation of anti–Jo-1 antisynthetase syndrome in a single Indian center. Methods and Materials: This was a medical records review single-center study that included patients with anti–Jo-1 antisynthetase syndrome over 10 years. Results: This study included 27 patients with anti–Jo-1 antisynthetase syndrome, with mean age of 40 ± 9.2 years and female preponderance (female-to-male ratio, 4:1). At presentation, the characteristic triad was present in only 4 patients. A majority presented with the incomplete form, with 2 clinical features (of triad) in 11 and single feature (of triad) being present in 12 patients at initial presentation. Seven presented only with polyarthritis, out of which 6 had been earlier diagnosed as rheumatoid arthritis. Time gap from diagnosis of "rheumatoid arthritis" to antisynthetase syndrome ranged from 3 to 20 years. In patients who had only arthritis in the beginning, there was a significantly longer delay to diagnosis of antisynthetase syndrome, higher frequency of rheumatoid factor, and lower frequency of anti–Ro-52. Overall, outcome was good, with Eastern Cooperative Oncology Group class 1 or 2 in most except 2 patients. Conclusions: Anti–Jo-1 antisynthetase syndrome commonly presented as incomplete (not a triad) and often only with arthritis. These patients are diagnosed and treated as rheumatoid arthritis for many years, before a diagnosis of antisynthetase syndrome is made. Being aware of this presentation may help in earlier diagnosis by actively searching for subtle clues.